2001
DOI: 10.1002/pola.1206.abs
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of trans???cis isomerization of the substituted azobenzene moiety bound on a liquid‐crystalline polymer

Abstract: A mechanistic study of the trans%cis isomerization of the azobenzene moiety in a side-chain liquid-crystal polymer system was carried out with six liquidcrystalline polymethacrylates in which different electron-withdrawing substituents were attached to the para-positions of the azobenzene chromophores. Compared to the non-nitro-substituted azo polymers, the nitro-substituted azo polymers exhibited two quite different behaviors: an extraordinarily high reaction rate of the thermal cis-trans isomerization and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…On absorbing a photon the planar trans isomer transforms into the bent and twisted cis form, the latter undergoing reverse transformation either by the same mechanism or by thermally induced back isomerization [1], see figure 1. The absorption bands for both photoisomerization processes depend on the chemical nature of the substituents R, R .…”
Section: Introductionmentioning
confidence: 99%
“…On absorbing a photon the planar trans isomer transforms into the bent and twisted cis form, the latter undergoing reverse transformation either by the same mechanism or by thermally induced back isomerization [1], see figure 1. The absorption bands for both photoisomerization processes depend on the chemical nature of the substituents R, R .…”
Section: Introductionmentioning
confidence: 99%
“…Studies using picosecond Raman and femtosecond fluorescence show a double bond (N=N) in the excited state, confirming the inversion mechanism (Fujino et al, 2001;Fujino and Tahara, 2000). In contrast, Ho et al (2001) found evidence that the pathway is compound-specific: a nitro-substituted azobenzene photoisomerized via the rotation pathway. Furthermore, ab initio and density functional theory calculations indicate that both pathways are energetically accessible, although inversion is preferred (Angeli et al, 1996;Jursic, 1996).…”
Section: Introduction To Azobenzenementioning
confidence: 72%
“…Regarding synthesis strategies, still the synthesis of chromophorecontaining monomer followed by polymerization remains the most convenient route. [17][18][19][20] However, most of the time, this method fails to realize high molecular weight and very often requires the use of comonomer that further complicates the situation. As the relaxation of oriented dipoles is the most important criteria for selection toward device fabrication, it is obvious that high molecular weight polymer is a must.…”
Section: Introductionmentioning
confidence: 98%
“…15,16 Azobenzene derivatives have widely been investigated as promising NLO materials 17,18 because of their high hyperpolarizability, easy methods of preparation, and better processibility. Regarding synthesis strategies, still the synthesis of chromophorecontaining monomer followed by polymerization remains the most convenient route.…”
Section: Introductionmentioning
confidence: 99%